Correlation between in situ structural and optical characterization of the semiconductor-to-metal phase transition of VO2 thin films on sapphire. Issue 2 (12th December 2019) - Cesca, Tiziana; Scian, Carlo; Petronijevic, Emilija; Leahu, Grigore; Li Voti, Roberto; Cesarini, Gianmario; Macaluso, Roberto; Mosca, Mauro; Sibilia, Concita; Mattei, Giovanni
Abstract : In situ XRD and IR optical measurements demonstrate the coexistence of M1 and R phases during the SMT transition of VO2 thin films. Abstract : A detailed structural investigation of the semiconductor-to-metal transition (SMT) in vanadium dioxide thin films deposited on sapphire substrates by pulsed laser deposition was performed by in situ temperature-dependent X-ray diffraction (XRD) measurements. The structural results are correlated with those of infrared radiometry measurements in the SWIR (2.5–5 μm) and LWIR (8–10.6 μm) spectral ranges. The main results indicate a good agreement between XRD and optical analysis, therefore demonstrating that the structural transition from monoclinic to tetragonal phases is the dominating mechanism for controlling the global properties of the SMT transition. The picture that emerges is a SMT transition in which the two phases (monoclinic and tetragonal) coexist during the transition. Finally, the thermal hysteresis, measured for thin films with different thickness, showed a clear dependence of the transition temperature and the width of the hysteresis loop on the film thickness and on the size of the crystallites.